OPTIMIZATION OF NEAR-INFRARED LED (NIR-LED) POSITION IN NON-INVASIVE BLOOD GLUCOSE AND CHOLESTEROL MEASUREMENTS: OPTIMASI POSISI NEAR-INFRARED LED (NIR-LED) PADA PENGUKURAN KADAR GLUKOSA DAN KOLESTEROL DARAH NON-INVASIF - Meisya Indri Yanti; Nur Jannah; Umiatin; Ernia Susana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Cardiovascular disease (CVD) is the leading cause of global mortality, with deaths from this disease projected to rise to 23.3 million by 2030. Along with the increasing prevalence of cardiovascular diseases, non-invasive methods for measuring blood glucose and cholesterol levels using optical sensors consisting of Near-Infrared (NIR) LEDs and photodiodes have been developed and become a critical aspect of monitoring the health conditions of CVD patients. This study aims to identify the optimal placement of the sensor and the ideal part of the finger to ensure maximum and accurate voltage readings by the photodiode. Data collection was conducted using a transmission measurement mode with 180º variations in sensor placement both vertically and horizontally. In the vertical position, the NIR-LED and photodiode were placed opposite each other above and below the finger, while in the horizontal position, they were placed opposite each other on the left and right sides of the finger. Five subjects participated in the characterization process. The test results showed that the vertical sensor placement yielded an average voltage reading of 0.1543V, higher than the horizontal placement, which recorded an average of 0.0702V. Voltage readings for different parts of the finger—thumb, index finger, middle finger, ring finger, and pinky finger—were recorded as 0.1543V, 0.2889V, 0.2223V, 0.2201V, and 0.2139V, respectively. Thus, it can be concluded from this study that vertical sensor placement on the index finger provides the maximum voltage reading. These findings serve as a reference for determining the optimal sensor position to enhance the accuracy of non-invasive blood glucose and cholesterol measurement devices.